2014
DOI: 10.3892/mmr.2014.2759
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoke affects dendritic cell maturation in the small airways of patients with chronic obstructive pulmonary disease

Abstract: The aim of the present study was to characterize and quantify the numbers and expression levels of cells markers associated with dendritic cell (DC) maturation in small airways in current smokers and non-smokers with or without chronic obstructive pulmonary disease (COPD). Lung tissues from the following 32 patients were obtained during resection for lung cancer: Eight smokers with COPD, eight non-smokers with COPD, eight current smokers without COPD and eight non-smokers without COPD, serving as a control. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 33 publications
1
23
0
2
Order By: Relevance
“…This is the first study to examine CCR7 mRNA expression in NSCLC patients in relation to smoking history, which revealed higher expression level in patients with a smoking status ≥ 40PYs (see Table 3). Previous studies focused on exposure of patient with chronic obstructive pulmonary disease to cigarette smoke have suggested that cigarette smoke may have an influence on CCR7 expression [15].…”
Section: Resultsmentioning
confidence: 99%
“…This is the first study to examine CCR7 mRNA expression in NSCLC patients in relation to smoking history, which revealed higher expression level in patients with a smoking status ≥ 40PYs (see Table 3). Previous studies focused on exposure of patient with chronic obstructive pulmonary disease to cigarette smoke have suggested that cigarette smoke may have an influence on CCR7 expression [15].…”
Section: Resultsmentioning
confidence: 99%
“…Similar approaches were undertaken by other authors [19,20] who demonstrated pathological changes instead of testing pulmonary function to demonstrate the validity of COPD model. In COPD, main pathological changes are in the small airways, and chronic inflammation is part of these changes [21]. COPD pathophysiology is closely related to infiltration of T lymphocytes in the airways and lung parenchyma [2].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, after smoking cessation, total DC levels were comparable to those of nonsmokers . Likewise, Liao et al demonstrated that, in the small airway, there was a modest decrease in the presence of CD83 + DCs in active smokers with compared with nonsmokers . Given our work demonstrating that smoke had opposing effects on each of the myeloid DC subsets, total myeloid DC counts may not give an accurate representation of tissue populations.…”
Section: Discussionmentioning
confidence: 53%